(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2014)
Mucilage was isolated from the seeds of Diospyros melonoxylon Roxb., a plant growing naturally in the forests of India. Various physico-chemical methods like particle analysis, scanning electron microscopy, differential scanning calorimetry, differential thermal analysis, thermogravimetry analysis, molecular weight by gel permeation chromatography, rheometry, elemental analysis, x-ray diffraction spectrometry, zeta potential, fourier transform infrared spectroscopy, 1D(1H and 13C) (NMR) have been employed to characterize this gum in the present study. Particle analyses suggest that mucilage had particle size in nanometer. SEM analysis suggested that the mucilage had irregular particle size. The glass transition temperature of the gum observed was 78 °C and 74 °C by DSC and DTA respectively. The Thermogravimetry analysis suggested that mucilage had good thermal stability with two stage decomposition. The molecular weight of mucilage was determined to be 8760, by gel permeation chromatography, while the viscosity of mucilage was observed to be 219.1 cP. The XRD pattern of the mucilage indicated a complete amorphous nature. Elemental analysis of the gum revealed specific contents of carbon, hydrogen, nitrogen and sulfur. The major functional groups identified from FT-IR spectrum include 3441 cm-1 (-OH), 1632 cm-1 (-COO-), 1414 cm-1 (-COO-) and 1219 cm-1 (-CH3CO). Analysis of mucilage by paper chromatography and 1D NMR indicated the presence of sugars.